Religious statecraft: Constantinianism in the figure of Nagashi Kaleb - Rukuni, Rugare (HTS teologiese studies, 2020)
The Himyarite invasion of 525 CE by Kaleb of Aksum was a definitive war in the narrative of global religion and politics. The accounts surrounding the war corroborate the notion of an impressed Constantinian modus of establishing religious statecraft. Whereas there has been much anthropological and archaeological work on the South Arabian–Aksumite relations from the 4th to the 6th centuries, revisionism in perspective of literary sources and respective evidence retains significance given the dynamism of Ethiopianism as a concept. Implicative document analysis, cultural historiography and archaeology of religion are relevant methods used in this study. There are parallels between Kaleb’s new Zion agenda and Constantine’s nova Roma persona, both resembling an emergent Christian-religious state. It is from this religious (Christian) state that a geopolitical policy that defined the trajectory of their respective nations emerged. The replete epigraphy and literary evidence on Ethiopia and its Byzantine connection aggregately affirms the explicit existence of a Christianised foreign policy.Contribution: The research revises the narrative of Ethiopian Christianity with a lens of political-religious dynamics thereby contributing to the field of theology and history.